2017
DOI: 10.1016/j.marpetgeo.2016.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for gas hydrate occurrences in the Canadian Arctic Beaufort Sea within permafrost-associated shelf and deep-water marine environments

Abstract: The presence of a wedge of offshore permafrost on the shelf of the Canadian Beaufort Sea has been previously recognized and the consequence of a prolonged occurrence of such permafrost is the possibility of an underlying gas hydrate regime. We present the first evidence for widespread occurrences of gas hydrates across the shelf in water depths of 60-100 m using 3D and 2D multichannel seismic (MCS) data. A reflection with a polarity opposite to the seafloor was identified ~1000 m below the seafloor that mimics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 48 publications
4
34
0
1
Order By: Relevance
“…Methods based on electrical properties of frozen vs. unfrozen ground were shown to be applicable in shallow coastal water, but results of these surveys require thorough validation by observational data [22,95]. Recently reported results [68] presented evidence for widespread occurrence of gas hydrates across water depths of 60-100 m on the shelf of the Canadian Beaufort Sea using 3D and 2D multichannel seismic data. However, any interpretation of data obtained using any methods should be validated by recovered sediment core analysis; this implies that widespread scientific drilling is required over the entire Arctic shelf, not only in the ESAS, in order to recover a sufficient number of sediment cores representative of different types of sediments and geological Some experimental work has been performed to investigate subsea permafrost physics, establishing the basis for improved modeling of subsea permafrost and associated processes.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods based on electrical properties of frozen vs. unfrozen ground were shown to be applicable in shallow coastal water, but results of these surveys require thorough validation by observational data [22,95]. Recently reported results [68] presented evidence for widespread occurrence of gas hydrates across water depths of 60-100 m on the shelf of the Canadian Beaufort Sea using 3D and 2D multichannel seismic data. However, any interpretation of data obtained using any methods should be validated by recovered sediment core analysis; this implies that widespread scientific drilling is required over the entire Arctic shelf, not only in the ESAS, in order to recover a sufficient number of sediment cores representative of different types of sediments and geological Some experimental work has been performed to investigate subsea permafrost physics, establishing the basis for improved modeling of subsea permafrost and associated processes.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…These studies showed that self-preservation in porous hydrates depends on host sediment properties, hydrate structure and saturation, salt and ice content of pore water, etc. [67,68]. Stability of these hydrates in the ESAS is determined by the dynamics of coupled pressure/temperature (P/T) conditions, which change drastically during the repeated freeze-thaw cycles experienced by a permafrost-hydrates system in glacial-interglacial epochs.…”
Section: Mechanism Of Arctic Hydrate Originationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ice-bonded permafrost and gas hydrate are found mainly in the Iperk sequence (Blasco et al, 1990;Hu et al, 2013). Gas hydrates are associated with thick permafrost, occurring to depths exceeding 1,200 m below seafloor (mbsf), deeper than the base of the relict permafrost Judge & Majorowicz, 1992;Riedel et al, 2017;Weaver & Stewart, 1982). The top of the gas hydrates zone presently partially overlaps with ice-bonded and ice-bearing sediments (Judge et al, 1987;Osadetz & Chen, 2010).…”
Section: Shelf Permafrost and Gas Hydratesmentioning
confidence: 99%
“…Chinese and international researchers have used it to conduct a number of related studies. Many geophysical and electromagnetic logging technologies were investigated for gas hydrate mineral deposits in the Mackenzie Delta in Canada and Alaska North Slope in the USA [3][4] . The Geological Survey of China has carried out geophysical exploration works and effectiveness experiments in the Muli area of Qilian Mountain, such as audio-frequency magnetotellurics, low frequency ground penetrating radar (GPR), surface nuclear magnetic resonance (NMR) method, and electromagnetic well logging technique [5] .However, after drilling, it is found that many identification marks are not completely related to natural gas hydrate deposits.…”
Section: Introductionmentioning
confidence: 99%